DYNAMICS OF NT-PROBNP PROTEIN STATE IN CHILDREN WITH CONGENITAL HEART DEFECTS - Khaydarov K.I., Usmanova D.U.,; Khamraeva G.Sh., (Central Asian Journal of Medicine, 2025)
Significant scientific results aimed at studying diagnostic and prognostic measures in Pediatric Critical Care Medicine (2022) have shown that IL-6, IL-1beta, IL-10 and TNF-alpha levels correlate with the development of postoperative systemic inflammatory response syndrome (SIRS) and acute complications. IL-33 levels are considered as a potential prognostic marker for the risk of pulmonary hypertension and cardiac failure after CABG interventions. Elevated levels of high-sensitivity troponin and NT-proBNP are associated with an increased risk of postoperative cardiac dysfunction. ST2 (interleukin suppressor) has been proposed as a prognostic marker for death or prolonged ventilatory support in neonates after open heart surgery (Journal of Thoracic and Cardiovascular Surgery, 2023).